Virological and Immunological Aspects of AIDS Pathogenesis - Brian Conway; Francisco J Diaz-Mitoma (Canadian Journal of Infectious Diseases)
The most common and serious problem associated with long term antiretroviral therapy is waning efficacy over time. To date. a number of studies has suggested an association between drug resistance and clinical deterioration. However. a precise causal relationship has yet to be demonstrated. In a large American clinical trial. resistance to zidovudine (ZDV) was predictive of subsequent disease progression if this therapy was continued. Surprisingly. this was also predictive of deterioration if therapy was changed to didanosine (ddl). This suggests that other factors (perhaps virological and immunological) which may be present in addition to resistance. were as important (if not more so) in predicting clinical outcomes. It is likely that viral load. resistance. viral phenotype and alterations in immune function interact in this regard. Proper· studies may allow us to determine a “threshold” for a composite virological and immunological parameter beyond which disease progression will occur. As more antiretroviral agents become available. we will be in a position to intervene to “improve” laboratory markers and monitor them prospectively. potentially to maintain clinical latency for an indefinite period of time. In the authors' laboratories, a quantitative polymerase chain reaction assay for the evaluation of circulating proviral load has been developed. In an initial study of 70 patients. proviral load/ 106 CD4 cells was clearly associated with the severity of immune disease. with up to 9.6% of cells being infected in subjects with CD4 cell counts below 200/µL. However. large variability in proviral load among individuals with comparable or dissimilar CD4 cell counts precludes the use of this measurement as an individual marker of the severity of immune disease. More recent work evaluated the combined use of proviral load (expressed as a dichotomous variable based on values above or below one copy/a03 CD4 cells) and resistance in a prospective fashion. In five patients with high proviral loads and isolates resistant to their current therapy. a mean decrease of 72 CD4 cells/µL was observed over 12 months of observation. In contrast. in six patients with low proviral loads and sensitive isolates. there was a mean increase of 43 CD4 cells/µL. It appears that virological markers are associated with immune disease progression in this small cohort of patients. The association appears most marked when the two virological parameters are considered together rather than individually. The association is not always a tight one. and this may relate to a number of unmeasured factors. including viral phenotype. plasma viremia. and the immune response to HIV infection. Additional work incorporating these parameters into analysis is currently underway in the authors’ centre.